Resolución de problemas Geométricos con la mediación de Minecraft Education Edition en niños de grado quinto de primaria con TDAH - Randy Zabaleta Mesino; Osvaldo Rojas Velásquez; Beatriz Avelina Villarraga Baquero (Mundo Fesc)
This paper describes an activity containing three problems of geometric notions. The phases of problem solving considered in Schoenfeld's TRU framework and the mathematical performance of students for each proposed problem are assessed, taking into account the basic learning rights (DBA 5) and (DBA 7) for fifth grade in the Colombian reference framework. It was applied to neurotypical students and those diagnosed with ADHD from the Mauricio Nelson Visbal educational institution in grade 5-02, in person, with the guidance of the teacher. Problem solving in metric and spatial thinking is analyzed. In addition, two students with ADHD in the same grade of schooling from the Docente de Turbaco educational institution participate in the activity, which they do with the mediation of the Microsoft Minecraft Education platform. Both institutions are located in the north of the department of Bolívar. The study adopts a qualitative approach through a participatory action research design. Students who developed the activity using the gamified resource Minecraft Education Edition and with the methodological considerations and strategies of the inclusive TDR model excelled in mathematical performance and also in mastering the phases of problem solving compared to students who did not use the technological resource.